Les « associations villageoises de jeunesse » en pays bété, Côte d’Ivoire - Léo Montaz (Ateliers d'Anthropologie)
This article examines the “village youth associations” that exist throughout Bété country, in the western centre of the Ivory Coast. In this lineage society strongly structured by primogeniture, the emergence of youth as an autonomous political category raises questions about the restructuring of the powers that run through the entire region. Based on debates surrounding these associations, the article proposes a method for analysing young people in conflict situations, using the “strategic group” concept proposed by the socio-anthropology of development. Analysis of contemporary dynamics will also make it possible to better describe democratisation processes in village political arenas, in relation to which the question of the citizenship of “subordinate” categories is considered, categories that are traditionally excluded from the political game.